Omecamtiv Mecarbil: A Myosin Motor Activator Agent with Promising Clinical Performance and New in vitro Results - Nanasi, Peter; Komaromi, Istvan; Gaburjakova, Marta; Almassy, Janos (Current Medicinal Chemistry, 2018)
Background: Clinical treatment of heart failure is still suffering from limited efficacy and unfavorable side effects. The recently developed group of agents, the myosin motor activators, act directly on cardiac myosin resulting in an increased force generation and prolongation of contraction. The lead molecule, omecamtiv mecarbil is now in human 3 stage. In addition to the promising clinical data published so far, there are new in vitro results indicating that the effect of omecamtiv mecarbil on contractility is rate-dependent. Furthermore, omecamtiv mecarbil was shown to activate cardiac ryanodine receptors, an effect that may carry proarrhythmic risk. Methods: These new results, together with the controversial effects of the drug on cardiac oxygen consumption, are critically discussed in this review in light of the current literature on omecamtiv mecarbil. Results: In therapeutically relevant concentrations the beneficial inotropic effect of the agent is not likely affected by these new results - in accordance with the good clinical data. At supratherapeutic concentrations, however, activation of cardiac ryanodine receptors may increase arrhythmia propensity, and the stronger effect on diastolic than systolic cell shortening, observed at higher pacing frequencies, may decrease or offset the inotropic effect of omecamtiv mecarbil. Conclusion: Further studies with definitely supratherapeutical concentrations of omecamtiv mecarbil should be designed to map the actual risk of these potentially harmful side-effects.
Keywords: inotropic agents